Strengthening Local Wisdom-Based Work Culture in Improving the Quality of Education in Madrasah - Rusmiyati, Rusmiyati; Z, Wan Jamaludin; Akmansyah, Muhammad; Hadiati, Eti (JURNAL AL-TANZIM, 2022)
This study aimed to improve the quality of madrasah education by strengthening the work culture of Madrasah Aliyah teachers in the western region of the Central Lampung district. This research uses a qualitative case study approach. Data collection techniques used are observation, interviews, and documentation. The data analysis technique uses Miles and Huberman's interactive analysis, which includes; the process of data collection, data reduction, data presentation, and conclusion. The results showed that improving the quality of madrasah education through strengthening the work culture of Madrasah Aliyah teachers was carried out through the implementation of work culture in planning, work culture in organizing, work culture in performance, and work culture in supervision, work culture in evaluation. This research has implications for the importance of a work culture that must be managed in such a way as to achieve the desired goals.